Interprofessionalism and its perceptions a study with participants of the Education through Work for Health Program (Research, Society and Development, 2021)
Objective: To understand the perceptions of the members of Education through Work for Health Program (PET- Health) about the concept and context of “interprofessionality”, in view of the relevance of the theme in the academic and professional environment. Methodology: The research is a qualitative study carried out through an in-depth interview in which an electronic device was used for recording and later, the interview was transcribed and submitted to the Lexical Mechanized Content Analysis technique with the aid of the IRAMUTEQ software that resulted in a corpus. The text segment defined five classes divided into two axes. Results: The general corpus consisted of 12 texts, separated into 142 text segments (ST) with 91 ST (64.08%). 5,094 occurrences (words, forms or words) emerged, 864 distinct words and 413 with a single occurrence. The text segments were sized and classified in the Descending Hierarchical Classification Analysis (CHD), which defined five classes divided into two axes. Axis 1, called constitution and practices of interprofessionality, composed of class 05 and; there is a discussion of the meanings of the practical dimension about interprofessionality presenting the actions and their composition; sub-axis 1.1, called the practical dimension of interprofessionality, which consists of classes 04 and 01; axis that is related to the conduct of the actions to be carried out; and axis 2, called concepts and functions of interprofessionality, formed by classes 02 and 03.Conclusion: It was found that the development of PET-Saúde, based on interprofessional education, contributes to a better training in health, with curricular integration, diversification of learning scenarios, articulation of the university with health services, ethical, humanistic and critical-reflexive dimension within an expanded understanding of health.